Association between sleep quality and body composition of health professionals at a university hospital (Research, Society and Development, 2023)
The article aims to evaluate the association between sleep quality and body composition of health professionals at the University Hospital of Teresina. It is a prospective cross-sectional study developed with health professionals from the University Hospital of the Federal University of Piauí. The study included health professionals from the HU UFPI of both sexes, aged between 20 and 59 years. The anthropometric measures evaluated were: weight, height, waist circumference (WC) and hip circumference (HC). The height weight assessment was used body mass index (BMI). Body composition assessment was performed using the Bioelectrical Impedance (BIA) method. The Pittsburg Sleep Quality Index (PSQI) was used to assess sleep. Descriptive analysis was performed to characterize the participants. Categorical variables were presented using frequencies and percentages, and quantitative variables using mean and standard deviation. To assess the association between the variables of interest, the Student's t test was performed. The significance level adopted was 5. As a result, 53 health professionals of both genders participated in this study, most of them female (83.0%), aged between 31 and 40 years (56.6%). Regarding professional training, 60.4% were nursing professionals, 16.9%. As for nutritional status, 58.5% of respondents were overweight or obese, according to BMI. It should be noted that most of the participants 60.4% have poor sleep quality, only 18.9% said it was good and 20.7% had sleep disorders.